Working Condition And The Convenience Of Organization Environment Related With Performance Of Pharmacist Assistant: DUKUNGAN ORGANISASI DENGAN KINERJA ASISTEN APOTEKER - kiswanto kiswanto (STIKes Hang Tuah Pekanbaru, 2017)
Organization support is one of the determining factors in improving the performance of the employees. Organization support consisting of organizational factor, convenience environment, the provision of the infrastructure the selection of technology and working proviso condition. The purpose of this study is to analyze the relationship between organization support and performance of pharmacist assistant at the pharmacies division of the district general hospital Arifin Achmad Pekanbaru of Riau province. This was an analytic quantitative study with the cross sectional design to 53 pharmacist assistants as population. The study was used total sampling. The data were collected by using questionnaire and analyzed with univariate and bivariate. The results showed 49% pharmacist assistants having poor performance. There was a significant relationship between working condition (p-value = 0,04), the convenience of organization environment (p-value = 0,019) with the performance of pharmacist assistant. Its Expected the hospital management to improve the convenience of organization environment at the pharmacies division and also improve the health program and salvation for pharmacist assistant.